Printed dry and ready-to-use in vitro diagnostic culture media devices for differentiation and antimicrobial susceptibility testing of bacteria - Dieter Spiehl; Gerhard Schwall; Fabian Post; Carina Weber; Edgar Dörsam; Andreas Blaeser; Volkhard A.J. Kempf; Michael Hogardt (Biosensors and Bioelectronics: X)
This work presents a ready-to use dry culture device platform for differentiation of bacterial species and testing antibiotic susceptibility conveniently. The study demonstrates that high-volume and scalable production methods such as can reliably manufacture such devices for reproducible in vitro diagnostic testing. This marks a significant advancement compared to similar handmade devices in the literature.Two types of ready-to-use (RTU) devices were produced through printing. One device differentiates bacterial species from urine samples for rapid diagnosis of urinary tract infections (UTI), while the other determines the minimum inhibitory concentration (MIC) of antibiotics against specific bacterial species. The results show performance comparable to standard tests in clinical microbiological laboratories. The differentiation of bacterial species from four UTI samples matched the efficacy of commercial UTI agar plates utilizing chromogenic substrates. The MIC determination for seven bacterial species in three independent tests yielded categorical results consistent with MIC test strips on agar plates as reference standard. Minor errors occurred in 14 % and major errors in 5 % of the tests. No major errors occurred and in 81 % of all tests results were correct and consistent with the reference method.